2013
DOI: 10.1002/fld.3868
|View full text |Cite
|
Sign up to set email alerts
|

An SPH model for free surface flows with moving rigid objects

Abstract: SUMMARYThis paper presents a computational model for free surface flows interacting with moving rigid bodies. The model is based on the SPH method, which is a popular meshfree, Lagrangian particle method and can naturally treat large flow deformation and moving features without any interface/surface capture or tracking algorithm. Fluid particles are used to model the free surface flows which are governed by Navier-Stokes equations, and solid particles are used to model the dynamic movement (translation and rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…It is promising to note that good progress has been made in recently years to understand the fundamentals of this phenomenon, as reported in Liang et al (2010), Chen et al (2013) and Liu et al (2014). More practical scenarios have been considered by Wu et al (2013), using a GPUbased WCSPH model to simulate dam-break flooding in urban areas.…”
Section: Model Application II -Three-dimensional Dam-break Flow With mentioning
confidence: 98%
See 1 more Smart Citation
“…It is promising to note that good progress has been made in recently years to understand the fundamentals of this phenomenon, as reported in Liang et al (2010), Chen et al (2013) and Liu et al (2014). More practical scenarios have been considered by Wu et al (2013), using a GPUbased WCSPH model to simulate dam-break flooding in urban areas.…”
Section: Model Application II -Three-dimensional Dam-break Flow With mentioning
confidence: 98%
“…Some studies even consider multi-degrees of the freedom, as documented by Bouscasse et al (2013), Liu et al (2014), Amicarelli et al (2015), Ren et al (2015) and Canelas et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the mesh-free Smoothed Particle Hydrodynamics (referred as SPH) method becomes quite attractive in simulating the violent deformation of free surface and the wave breaking. As a result, a variety of fluid-structure interaction problems have been investigated by using either SPH (Gao et al, 2012;Liu et al, 2014;Ren et al, 2014) or other similar mesh-free particle models (Koshizuka et al, 1998;Hwang et al, 2014). SPH was originally developed for the astrophysical computations by Gingold and Monaghan (1977) and later modified to model the fluid flows by Monaghan (1994).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the continuity and momentum conservation equations are formulated as a set of ordinary differential equations, and the SPH particle positions and attributes are computed by using the standard numerical integration methods in the time domain. With regard to the water entry problem, there exist quite a few good SPH works including Vandamme et al (2011), Skillen et al (2013) and Liu et al (2014). It has been found that the SPH method is quite promising in simulating these kinds of transient impact problems and very refined flow features can be captured by the mesh-free particle motion.…”
Section: Introductionmentioning
confidence: 99%
“…A variable mass approach has also been used by Omidvar et al (2012) for the study of more practical wave-solid interactions, as the computational efficiency was greatly improved due to the adoption of non-uniform particle configurations. The latest fluid-structure interaction work was reported by Liu et al (2014a), in which more advanced kernel corrections and solid boundaries were used to improve the numerical performance. In the incompressible SPH (e.g.…”
Section: Introductionmentioning
confidence: 99%